Combined Uses of Two Kinds of LASERS Nd-YAG and Er-YAG in Treatment of Oral Fibroma and Pathological Evaluation of Obtained Samples: Case Report - AM - Shirani; M Razavi; Gh Feizi (Isfahan University of Medical Sciences, 2005)
Today, the laser is used in a wide range of dental procedures. Some of the advantages of some lasers in treatment of oral soft tissue lesions are: elimination of need for local anesthesia, minimal bleeding, fast healing, absence of postoperative complications and reduction of recurrence rate. For these reasons is was used for treatment of oral fibroma.To our knowledge this is the first time both Nd: YAG and Er: YAG lasers was used for biopsy of oral fibroma in Iran. Oral fibroma was removed by these two lasers and examined by pathologist. The patient had no pain without using any local anesthesia. While using Nd: YAG laser, bleeding was not seen but cutting of tissue was slower than using blade . When using Er: YAG, cutting of tissue was faster than previous laser but bleeding could be seen.Key words. Fibroma, Nd-YAG laser, Er-YAG laser, Pathology.